The epidemiology of mild traumatic brain injury: the Trondheim MTBI follow-up study - Skandsen, Toril (Scand J Trauma Resusc Emerg Med, 2018)
BACKGROUND: Mild traumatic brain injury (MTBI) is a frequent medical condition, and some patients report long-lasting problems after MTBI. In order to prevent MTBI, knowledge of the epidemiology is important and potential bias in studies should be explored. Aims of this study were to describe the epidemiological characteristics of MTBI in a Norwegian area and to evaluate the representativeness of patients successfully enrolled in the Trondheim MTBI follow-up study. METHODS: During 81 weeks in 2014 and 2015, all persons aged 16–60 years, presenting with possible MTBI to the emergency department (ED) at St. Olavs Hospital, Trondheim University Hospital or to Trondheim municipal outpatient ED, were evaluated for participation in the follow-up study. Patients were identified by CT referrals and patient lists. Patients who were excluded or missed for enrolment in the follow-up study were recorded. RESULTS: We identified 732 patients with MTBI. Median age was 28 years, and fall was the most common cause of injury. Fifty-three percent of injuries occurred during the weekend. Only 29% of MTBI patients were hospitalised. Study specific exclusion criteria were present in 23%. We enrolled 379 in the Trondheim MTBI follow-up study. In this cohort, Glasgow Coma Scale score was 15 at presentation in 73%; 45% of patients were injured under the influence of alcohol. Patients missed for inclusion were significantly more often outpatients, females, injured during the weekend, and suffering violent injuries, but differences between enrolled and not enrolled patients were small. CONCLUSION: Two thirds of all patients with MTBI in the 16–60 age group were treated without hospital admission, patients were often young, and half of the patients presented during the weekend. Fall was the most common cause of injury, and patients were commonly injured under the influence of alcohol, which needs to be addressed when considering strategies for prevention. The Trondheim MTBI follow-up study comprised patients who were highly representative for the underlying epidemiology of MTBI.